Construing journeys to recovery from psychosis: A qualitative analysis of first‐person accounts. (7th June 2022) - Green, Bob; García‐Mieres, Helena
Abstract: Purpose: To perform a qualitative analysis of the factors that were construed as salient in facilitating the process of recovery in the narratives of people with psychosis who had their first‐person accounts (FPAs) published in an academic journal. Methods: Computerized textual analysis was undertaken of 156 FPAs written by persons who had experienced psychosis and published in the Schizophrenia Bulletin between 1979 and 2020. Constructs were extracted from the FPAs and coded in terms of Mental health treatment and therapy, Self‐management and Multiple factors; recovery processes (Connectedness, Hope, Identity, Meaning and Empowerment), Struggles and Turning points. Results: Psychosis impacted on individuals in profound and diverse ways. This was reflected in the different pathways to recovery included in the FPAs. Underlying the different pathways was the salience of re‐engagement in the shared reality of others; development of a cohesive and positive self; empowerment through the use of self‐management strategies, and making sense of experience through reconstruing what was meaningful. Personal constructs identified in the FPAs provided insight into both challenges faced and alternative avenues of movement that were perceived as available. Conclusions: Processes that support individuals re‐engaging with the shared reality of others are central to recovery. Supportive relationships and fostering open dialogue were consistent themes across the different pathways that recovery journeys took. Establishing a meaningful lifestyle and recovering a positive sense of identity were a key challenge following psychosis onset. Appreciation of experiences contained in FPAs has the potential to enhance the effectiveness and humanity of mental health care.